Fostering English Vocabulary Learning Through Mnemonics (2023)
ABSTRACT: The present Action Research study explores the implementation of mnemonic strategies at Institución Educativa Gilberto Alzate Avendaño. The project was conducted with sixth-grade students. The aim of the project was to foster effective English vocabulary learning through visual and linguistic mnemonics. The data collection tools included pre and post-tests, a questionnaire, an individual interview with students, and an interview with the cooperating teacher. Data was analyzed, categorized, and validated by using a triangulation method. The results show how the implementation of visual mnemonics had a positive effect on students' vocabulary learning. On the contrary, the linguistic mnemonic implemented was not as effective for learning English vocabulary in this context.